Art Therapy and Autism: A Picture of the Literature - Guardino, Caroline; Wallis, Rebekah; Harrison, Arien Peppers; Green, Morgan (Journal of the American Academy of Special Education Professionals, 2024)
Art therapy is an alternative therapeutic intervention implemented with individuals with autism spectrum disorders (ASD). Researchers, therapists, and parents suggest that art therapy is an effective treatment for targeting social and communicative behaviors. However, there is a paucity of evidence-based research to support this claim. A systematic literature review of peerreviewed studies was conducted to determine the effect of art therapy on students with ASD,ages 4-21 years. Nineteen studies met the inclusion criteria. A summary and analysis of the research are presented with specific strategies and outcomes of art therapy identified as an effective treatment method. Nine of the studies reviewed are of qualitative design: observational case studies with one or two participants; with the remaining six studies using quantitative research methods. Implications for researchers and practitioners are discussed.